Morphological and molecular analysis of Henneguya lagunensis n. sp. (Cnidaria, Myxosporea) parasitizing the gills of Eugerres brasilianus from Brazil - de Azevedo, Rodney Kozlowiski (2021)
Plasmodia containing myxospores belonging to the genus Henneguya Thélohan, 1892 were found in the gills of Eugerres brasilianus (Cuvier, 1830). Despite the economic importance, few parasitological studies have been done with this species. We describe Henneguya lagunensis n. sp. using morphological and molecular data. The mature myxospores were rounded, measuring 29.1 ± 2.2 μm in total length, 8.2 ± 1.0 μm in body length, 7.9 ± 0.2 μm in body width, 20.7 ± 2.4 μm in tail length and 4.8 ± 1.0 μm in thickness. The polar capsules measured 3.3 ± 0.4 in length and 1.7 ± 0.3 μm in width. Polar filaments had 4–5 turns, helical. Phylogenetic analysis showed Henneguya lagunensis n. sp. as a sister species of Henneguya cynoscioni Dyková, Buron, Roumillat and Fiala, 2011, within a clade that contained mostly Henneguya species that parasitize marine fish of the order Perciformes. This is the first report of a species of Henneguya parasitizing Eugerres brasilianus.